2017
DOI: 10.15171/jlms.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Modification on Viability of L929 Cells on Zirconia Nanocomposite Substrat

Abstract: IntroductionTitanium and its alloys as a dental implant have shown a high successful rate.1 Most metals or alloys are prone to corrosion process. Therefore, management and control of corrosion is a crucial point from biological aspects and may not limit to a local problem because the produced particles may migrate to far sites from the implant. Also it is important in terms of biocompatibility.2 So, the inert ceramic materials were suggested as alternatives to metals.3 Zirconia ceramic has been included in den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…It was suggested that laser irradiation produced adequate surface roughening of zirconia to support osseointegration 49) . It is noteworthy that another study showed that laser surface treatment showed positive effect on the viability of L929 cells 50) . Recently, micro-structured and nano-structured zirconia surfaces with higher surface roughness fabricated by solid-state laser sculpting were investigated.…”
Section: Laser Irradiationmentioning
confidence: 96%
See 1 more Smart Citation
“…It was suggested that laser irradiation produced adequate surface roughening of zirconia to support osseointegration 49) . It is noteworthy that another study showed that laser surface treatment showed positive effect on the viability of L929 cells 50) . Recently, micro-structured and nano-structured zirconia surfaces with higher surface roughness fabricated by solid-state laser sculpting were investigated.…”
Section: Laser Irradiationmentioning
confidence: 96%
“…Zirconia in dentistry has gained a vast amount interest in the last decade, having found its applications in prosthetic and implant dentistry. Laboratory studies have been focusing on modification of physico-chemical surface properties of zirconia for cementation 64,[102][103][104][105][106][107][108] zirconia porcelain bonding 109) and also to improve the biological performance of zirconia materials 39,41,50) . The results above have showed that many proposed surface treatment methods might improve the biological performance of zirconia used as a dental restoration or implant fixture.…”
Section: In Summarymentioning
confidence: 99%
“…Aivazi et al 123 reported the laser method for the modication of the surface to support osseointegration. In this study, surface modication caused a positive impact on the viability of broblast L929 cells.…”
Section: Review Nanoscale Advancesmentioning
confidence: 99%
“…Methods such as sandblasting, acid etching, and laser etching have been performed for this purpose. 122 Aivazi et al 123 reported the laser method for the modification of the surface to support osseointegration. In this study, surface modification caused a positive impact on the viability of fibroblast L929 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber lasers, which can make 2 µm-wide grooves, were proved to produce adequate roughness on zirconia surfaces and increase new bone formation and mechanical strength on the bone-implant interface (36). Additionally, laser technologies positively affect wettability, acting as a critical determinant of cell adhesion, proliferation, and calcification, contributing to accelerating zirconia osseointegration (37,38). Studies showed that laser treatment would not exhibit phase transformation to zirconia while improving mechanical properties (39,40).…”
Section: Lasermentioning
confidence: 99%